THE DETERMINANTS OF LIVELIHOOD INCOME DIVERSIFICATION AMONG RURAL FARMING HOUSEHOLDS IN OSUN STATE, NIGERIA. (FUDMA JOURNAL OF SCIENCES, 2021)
Rural economy in Nigeria is worst hit with the erratic and unpredictable factors that affect agricultural practice which is the main livelihood of the rural farm households. Consequently, farmers are left with the option of sourcing other means of survival to cope with the hard times due to in consistent and seasonal distribution of income which characterize small farm holders in sub-Saharan African countries. This study investigates the factor influencing the livelihood income diversification among rural farm households in Osun state, Nigeria. Multi stage sampling techniques was employed to sample120 structured and pre-tested questionnaires from 120 rural farm households. Descriptive statistics and multiple regression analysis were used to analyze the data. The results of the descriptive statistics revealed that household heads of age range 50-60 years are 38.6% and about 40.70% had primary education while 26.30% had no education. About 98.31% of the rural households engaged in farming out of which 80.57% have farm size ranging between 1-3 hacters. Logit regression analysis shows that access to credit was positively significant (P
Keywords: Determinant Livelihood, Income, Diversification, Nigeria